Evaluation of the teaching and learning in listening subject - Nurlaila Husain (TRANSBAHASA, 2020)
This present study is conducted to evaluate the teaching of listening skills in the English Department at Gorontalo State University. Evaluation in this study is to benchmark the current practice of teaching listening in the English Department of State University of Gorontaloto the research-based practice. Research finding suggests that the teaching of listening to the English Department students partly has followed methodologies proposed by Richards and Goh (2008). This study shows that in general the practice of the teaching of listening at the English Department of State University of Gorontalo is based on research-based methodologies. However, there are some points that need to be improved. Since the result of the study has addressed only some of the issues in the teaching of listening, therefore, future research on other issues of listening teaching needs to be done.